Uncommon type [compact disc, unabridged] : some stories - Hanks, Tom (Random House Audio, 2017)
A collection of 17 short stories by two-time Oscar winning actor Tom Hanks. A gentle Eastern European immigrant arrives in New York City after his family and his life have been torn apart by his country's civil war. A man who loves to bowl rolls a perfect game--and then another and then another and then many more in a row until he winds up ESPN's newest celebrity, and he must decide if the combination of perfection and celebrity has ruined the thing he loves. An eccentric billionaire and his faithful executive assistant venture into America looking for acquisitions and discover a down and out motel, romance, and a bit of real life.